Oral epithelium in diabetics: A cytomorphometric correlation - K P Nandita (Dental Hypotheses, 2014)
Objectives: The study aims to establish an etiological association between diabetes and precancerous lesions of the oral cavity by cytomorphometric analysis of the oral epithelium. Study Design: Smears were obtained from three distinct oral sites - buccal mucosa, dorsum of the tongue and the floor of the mouth in ten controls and ten patients previously diagnosed with type II diabetes. The oral smears were stained with Papanicolaou SA-36 solution. An eye - piece graticule was used to obtain the cytoplasm and nuclear dimension; where larger dimension was denoted as "D" and the smaller dimension was denoted as "d". The nuclear area (NA), nuclear diameter (ND), cytoplasmic area (CA) and the cytoplasmic / nuclear ratio (C/N) were evaluated from 50 cells predominant in each oral site. Statistical Analysis: The cytomorphometric data obtained was compared between the group of diabetic patients and the control groups using the student′s t- test (SPSS version 11.0). Results: Results showed that the nuclear area and the nuclear diameter of oral epithelial cells were increased in diabetic patients, as compared to non- diabetics, while the non- diabetic patients demonstrated an increase in nuclear ratio. Conclusions: The results from this study suggest that diabetes mellitus can cause alterations in oral epithelial cells that are detectable with exfoliative cytology.